Optimizing specialized nursing education in India for enhanced patient care quality: a nurse-patient centric approach - Kumari, Ritu; Singh Choudhary, Arun; Umar, Mohammed; S., Karthika; Chauhan, Amit; Suhashini; Priya, Tanu (International Journal of Research in Medical Sciences, 2025)
India’s nursing workforce is central to national health goals, yet nursing education remains largely generalist. Specialized education, emphasizing a nurse-patient centric approach, is essential to improving care quality and system efficiency. A systematic review was conducted across open-access databases (PubMed, BMJ Open and PKP) from 2015-2025 using PRISMA methodology. Studies on nursing specialization, curriculum reform, nurse-patient dynamics, and Indian policy frameworks were included. Data from 28 studies were thematically analyzed. Evidence supports that specialized nursing education improves clinical outcomes, patient satisfaction, and workforce competence. Major barriers include outdated curricula, insufficient faculty training, and fragmented regulatory oversight. The national education policy (NEP) 2020 and national nursing and midwifery commission (NNMC) bill present reform opportunities. Global models integrating clinical simulation, communication skills, and interdisciplinary learning show promising results. Optimizing specialized nursing education is crucial to addressing India’s diverse and evolving patient care demands. A patient-centered model that includes competency-based curricula, faculty development, and policy alignment can enhance both nurse performance and patient outcomes. India must prioritize infrastructure, policy reform, and academic innovation to empower its nursing cadre and improve healthcare delivery.